2011
DOI: 10.2215/cjn.10681210
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Testosterone, Endothelial Dysfunction, and Cardiovascular Events in Men with Nondialysis Chronic Kidney Disease

Abstract: SummaryBackground and objectives Deterioration of kidney function impairs testosterone production, with hypogonadism being common in men with chronic kidney disease (CKD). In nonrenal populations, testosterone is suggested to participate in the atherosclerotic process. In male dialysis patients, we showed that low testosterone increases the risk of mortality. We here studied plausible links among testosterone levels, vascular derangements, and cardiovascular events in nondialysis CKD men.Design, setting, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
86
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 33 publications
8
86
1
Order By: Relevance
“…Since T concentrations can decline by 30% as the day progresses, this would falsely increase the prevalence of subnormal T concentrations. Overall, the literature suggests that approximately half of men with ESRD have low total T concentrations and approximately one-third of men with milder forms of renal failure have low total T. These studies also found that the total T concentrations were lower in men with type 2 diabetes and CKD as compared to men without diabetes and CKD (10,11,12,29). These studies have used immunoassays to measure total T concentrations in men with CKD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Since T concentrations can decline by 30% as the day progresses, this would falsely increase the prevalence of subnormal T concentrations. Overall, the literature suggests that approximately half of men with ESRD have low total T concentrations and approximately one-third of men with milder forms of renal failure have low total T. These studies also found that the total T concentrations were lower in men with type 2 diabetes and CKD as compared to men without diabetes and CKD (10,11,12,29). These studies have used immunoassays to measure total T concentrations in men with CKD.…”
Section: Discussionmentioning
confidence: 93%
“…Total T concentrations are decreased in men with chronic kidney disease (CKD) (8,9,10,11,12,13). Endocrine society considers CKD and type 2 diabetes as conditions associated with a high prevalence of low T concentrations (5).…”
mentioning
confidence: 99%
“…26,27 Yılmaz et al reported lower levels of testosterone in patients with CKD, even at early stages of the disease. 28 In our group of patients with CKD, the serum levels of testosterone were significantly lower than the control group. Although mean serum testosterone levels were lower in group 1 than group 2, there was no statistical difference between both groups with CKD.…”
Section: Discussionmentioning
confidence: 52%
“…The degree of ED was divided into five categories: no ED (scores of [26][27][28][29][30], mild (scores of [22][23][24][25], mild-to-moderate (scores of 17-21), moderate (scores of [11][12][13][14][15][16], and severe (scores of 6-10). 12 Groups were composed as follows: group1: patients with CKD and ED; group 2: patients with CKD without ED; group 3: control patients without CKD or ED.…”
Section: Methodsmentioning
confidence: 99%
“…Because testosterone is an efficient anabolic hormone, its deficiency causes not only problems related to libido but also several important cardiometabolic side effects. These side effects include deterioration in cognitive functions, decrease in muscle mass, endothelial dysfunction, cardiovascular events, and an increase in the risk of death [25][26][27][28]. In a study conducted on 1822 male patients, Haring et al [28] demonstrated that low levels of total testosterone significantly increased mortality.…”
Section: Discussionmentioning
confidence: 99%